Design and development of a low cost and reliable writing aid for visually impaired based on Morse code communication. - Juneja, Sagar; Joshi, Pratyaksh (Technology & Disability, 2020)
There are a lot of assistive devices available for visually challenged people to make them self-dependent, but not many writing aids are available that could allow them to have written communication. Assistive devices also suffer from problem of low acceptance rate primarily because they are complex to use, have big cognitive load and are mostly expensive. This paper presents a low cost, portable and easy to use pen like writing aid for visually challenged people based on Morse code communication. Intelligent electronic hardware design has been carried out to make the device light weight and low cost with bill of materials (BOM) of electronic components is only $14. To make the device respond faster, a platform independent and novel software algorithm has been developed that runs on a microcontroller. Average speed of writing with the device is 70–80 characters per minute. It is a low power device with maximum rated voltage and current requirements of 5 V and 100 mA respectively. It is an easy to use and easy to hold device because it is designed in a pen like structure with the help 3D designing software and is made with light weight thermoplastic material using 3D printing technology.